2008
DOI: 10.1021/cr0782269
|View full text |Cite
|
Sign up to set email alerts
|

Salvinorin A Analogs as Probes in Opioid Pharmacology

Abstract: Recently, the biosynthetic route of 2a was studied using the incorporation of [1-13 C]glucose, [CH 3-13 C]methionine, and [1-13 C;3,4-2 H 2 ]-1-deoxy-D-xylulose into its structure. 58 Neoclerodane 2a, like other terpenoids, results from the assembly of isopentenylpyrophosphate and dimethylallyl pyrophosphate to form geranylgeranyl pyrophosphate (31) (Figure 4). 59 Cyclization of 31 affords the labdanyl cation (32), which after several methyl shifts yields clerodane pyrophosphate (33). Further oxidation, acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
95
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 101 publications
1
95
0
2
Order By: Relevance
“…Until recently, the most specific of these compounds were U69,593, U50,488 and their congeners spiradoline and enadoline, which have limited efficacy following oral administration Endoh et al 1999). In a recent report, Prisinzano and Rothman (2008) suggested that analogs of the chemicals isolated from S. divinorum may prove to be excellent research tools and give greater insight into opioid receptor-mediated phenomena. Some synthetic analogs of salvinorin A with altered pharmacology have recently been reported (partial agonists and antagonists).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, the most specific of these compounds were U69,593, U50,488 and their congeners spiradoline and enadoline, which have limited efficacy following oral administration Endoh et al 1999). In a recent report, Prisinzano and Rothman (2008) suggested that analogs of the chemicals isolated from S. divinorum may prove to be excellent research tools and give greater insight into opioid receptor-mediated phenomena. Some synthetic analogs of salvinorin A with altered pharmacology have recently been reported (partial agonists and antagonists).…”
Section: Discussionmentioning
confidence: 99%
“…1), was identified as a potent and highly selective κOR agonist (18). The structural novelty of Sal A led to extensive structure-activity relationship (SAR) studies through hemisynthetic approaches (19). The furyl-δ-lactone group of Sal A ( Fig.…”
mentioning
confidence: 99%
“…Numerous structure-activity relations (SAR) studies have been carried out on opioid receptor ligands to determine features that drive affinity or efficacy with the goal of generating more effective therapeutic compounds, (Eguchi 2004;Metcalf and Coop 2005;Prisinzano and Rothman 2008;Yongye, Appel et al 2009, amongst others). SAR studies employing site-directed substitutions and constraints of endogenous peptides, as well as modifications of morphine have provided valuable insights about the pharmacophoric features, ligand selectivity and biological roles of opioid receptors.…”
Section: Pharmacophoric Features Of Opioid Ligandsmentioning
confidence: 99%